Diffusion multiple study of Co-Ni-Ti system at 1073 K. (December 2018) - Yuan, Yuan; Yang, Li; Li, Dajian; Tang, Aitao; Pan, Fusheng; Seifert, Hans; Moelans, Nele
Abstract: Co-Ni-Ti system is a key system in many industrial applications. The thermodynamic and kinetic information of this system is crucial to alloy and process design. Although the system has been studied largely, there is still confusion about the stability of the ternary phase τ_Ti(Ni0.5Co0.5)3 phase, and only few data on the diffusion in the intermediate compounds as available. In this work, high throughput diffusion multiple approach was applied to investigate the isothermal section and interdiffusion in this system at 1073 K. The stability of the ternary phase τ_Ti(Ni0.5Co0.5)3 at 1073 K was confirmed based on detailed EPMA element mapping and XRD analysis. A scheme of the isothermal section of the Ni-Co-Ti system at 1073 K including the new findings is presented. The parabolic growth constant of intermediate phases of the binary Ni-Ti and Co-Ti systems at 1073 K were also calculated and the corresponding integrated interdiffusion coefficients were determined using integrated Wagner equations.